ANALISIS KEMACETAN LALU LINTAS PADA RUAS JALAN NASIONAL MAUMERE – LARANTUKA (KELURAHAN GELITING KECAMATAN KEWAPANTE) KABUPATEN SIKKA - MAUMERE - Riki Yohanes Moat; Yosef Norbertus Tembu Muda; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2023)
Kewapante District is one of the sub-districts in Sikka Regency with a population of 14,906 inhabitants (BPS Sikka Regency, 2022). With the large number of residents in Kewapante District, this will have an impact on increasing demand and becoming a center of activity both in socio-cultural activities, political activities, educational activities, and economic activities. On the MaumereLarantuka National road section, precisely Geliting, is an area that is crowded with motorized vehicles, at that location there is also a market so that high side barriers often occur and indirectly affect traffic flow and performance on these roads. As a state road that is often traversed by vehicles in Kewapante District, Sikka Regency, precisely on the MaumereLarantuka National road, the conditions in the field are very different. The purpose of this research is to evaluate road performance in the presence of a market. Regarding the method used to analyze the performance of the road section, the Indonesian Road Capacity Guidelines (PKJI 2014) are used, especially for urban roads. The survey was conducted for 3 (three) days, namely from Thursday, Friday and Saturday. From the survey results for three days and an analysis was carried out, it was found that the total peak volume was 1740 skr/hour, the capacity was 1771 skr/hour, the total Side Barrier was 549 events/hour and the value of the Degree of Saturation was 0.98, it can be concluded that the level of service the path is at level E. Keywords: Road Performance, Traffic Volume, Side Barriers, Degree of Saturation, Road Geometrics